IMPROVING STUDENTS’ ACHIEVEMENT IN READING EXPOSITION TEXTS THROUGH THE APPLICATION OF TWO STAY - TWO STRAY STRATEGY - Winda Syafitri (Universitas Potensi Utama, 2018)
The objective of this study is to investigate whether the application of Two Stay - Two Stray strategy significantly improves the students’ achievement on reading comprehension exposition text. This study was conducted by using classroom action research. The subject of this research was the second grade of SMA Negeri 2 Binjai which consisted of 36 students. The research was conducted in two cycles. The first cycle consisted of three meetings and second cycle consisted of three meetings. The instrument for collecting the quanitative data was essay test for reading and the instruments for collecting the qualitative data were diary notes, observation sheet, questionnaire sheet, interview sheet and students’ activities record. Based on the analysis, students’ achievement is improved in every test. In test I, the mean score was 56.44. In test II in cycle I, the mean score was 69.89, and in the test III in cycle II, the mean score was 81.58. Based on the observation sheet, diary notes, and interview sheet, it was found that the teaching learning process ran well. the students were more active, enthusiastic in working in group . It was concluded that Two Stay-Two Stray Strategy can improve the students’ achievement in reading exposition text.